Can New Keynesian Models Survive the Barro-King Curse? - Guido Ascari; Louis Phaneuf; Eric Sims (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
Barro and King (1984) conjecture that shocks other than those to total factor productivity will have difficulty generating key business cycle comovements between output, consumption, investment and hours worked. Recent years have seen the emergence of a class of DSGE models in which aggregate fluctuations are driven by several shocks, making them particularly vulnerable to the "Barro-King Curse". These models emphasize monopolistically competitive goods and labor markets, nominal rigidities and real frictions. We show that the standard medium-scale New Keynesian model is vulnerable to the curse predicting anomalous contemporaneous correlations between key variables and wrong profiles of cross-correlations. With the realistic additions of roundabout production and real per capita output growth, the New Keynesian model can survive the curse despite standard preferences and positive trend inflation.
Keywords: 330